If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(12x + 2) = log(2x + -1) + 1 Reorder the terms: glo(2 + 12x) = log(2x + -1) + 1 (2 * glo + 12x * glo) = log(2x + -1) + 1 (2glo + 12glox) = log(2x + -1) + 1 Reorder the terms: 2glo + 12glox = glo(-1 + 2x) + 1 2glo + 12glox = (-1 * glo + 2x * glo) + 1 2glo + 12glox = (-1glo + 2glox) + 1 Reorder the terms: 2glo + 12glox = 1 + -1glo + 2glox Solving 2glo + 12glox = 1 + -1glo + 2glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'glo' to each side of the equation. 2glo + glo + 12glox = 1 + -1glo + glo + 2glox Combine like terms: 2glo + glo = 3glo 3glo + 12glox = 1 + -1glo + glo + 2glox Combine like terms: -1glo + glo = 0 3glo + 12glox = 1 + 0 + 2glox 3glo + 12glox = 1 + 2glox Add '-2glox' to each side of the equation. 3glo + 12glox + -2glox = 1 + 2glox + -2glox Combine like terms: 12glox + -2glox = 10glox 3glo + 10glox = 1 + 2glox + -2glox Combine like terms: 2glox + -2glox = 0 3glo + 10glox = 1 + 0 3glo + 10glox = 1 Reorder the terms: -1 + 3glo + 10glox = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + 3glo + 10glox = 0 The solution to this equation could not be determined.
| 16xy+x^2+64y^2=0 | | 4+1f=17 | | 4k-12-6k=2k-6+6k+2 | | ln(2-1)=0 | | 4k-12-6=2k-6+6k+2 | | x^3-4x^2+6x=0 | | 8-3d=12 | | 432=-16t^2+64t+512 | | 2x^5-3x^4-2x^3+7x^2-2x-6=0 | | c^2-16h^4=0 | | 6r+3-2t+4=5 | | cosh(x)*cos(x)=1 | | 90=60+t | | -3b+23=80 | | 90=60t | | 2(k-4)=5k+2 | | x-4x-3=0 | | 2(k-4)=5k-2 | | 17x+7x=14-36 | | -4x-1+6x+4= | | 8(r-5)(r+5)=0 | | -4x+2+7x+3= | | 9x+4x-8x=8+7 | | 2(x-3)=(2x+5) | | 6y+2(3+6.5y)=2.5+15.5y | | 3+1b=5 | | 11p-9+8p-7+14=12p+9p+4 | | 8x-24y=144 | | 0.5r+5.2=2.8 | | 7(24-x)=5x | | 4x^2-2ax-2bx+ab=0 | | 12-k=22 |